Accelerating skin regeneration and wound healing by controlled ROS from photodynamic treatment - Khatereh Khorsandi; Reza Hosseinzadeh; HomaSadat Esfahani; Kavosh Zandsalimi; Fedora Khatibi Shahidi; Heidi Abrahamse (BMC, 2022)
Abstract Cellular metabolisms produce reactive oxygen species (ROS) which are essential for cellular signaling pathways and physiological functions. Nevertheless, ROS act as "double-edged swords" that have an unstable redox balance between ROS production and removal. A little raise of ROS results in cell proliferation enhancement, survival, and soft immune responses, while a high level of ROS could lead to cellular damage consequently protein, nucleic acid, and lipid damages and finally cell death. ROS play an important role in various pathological circumstances. On the contrary, ROS can show selective toxicity which is used against cancer cells and pathogens. Photodynamic therapy (PDT) is based on three important components including a photosensitizer (PS), oxygen, and light. Upon excitation of the PS at a specific wavelength, the PDT process begins which leads to ROS generation. ROS produced during PDT could induce two different pathways. If PDT produces control and low ROS, it can lead to cell proliferation and differentiation. However, excess production of ROS by PDT causes cellular photo damage which is the main mechanism used in cancer treatment. This review summarizes the functions of ROS in living systems and describes role of PDT in production of controllable ROS and finally a special focus on current ROS-generating therapeutic protocols for regeneration and wound healing.